2022
DOI: 10.1080/21655979.2022.2068781
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA T cell leukemia homeobox 1 neighbor enhances signal transducer and activator of transcription 5A phosphorylation to promote colon cancer cell invasion, migration, and metastasis

Abstract: Colon cancer is among the most prevalent gastrointestinal tumor types. The long noncoding RNA (lncRNA) T cell leukemia homeobox 1 neighbor (TLX1NB) is up-regulated in colorectal cancer (CRC). However, the functional role of this lncRNA in colon cancer remains unknown. In our study, we investigated the clinical significance of TLX1NB in colon cancer through bioinformatics analysis and explored its role in migration, invasion and metastasis of colon cancer cell with a series of experiments. Firstly, TLX1NB was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Further, they concluded that TLX1NB may be an early biomarker for the recurrence of low-grade gliomas. Chen et al ( 46 ) found that the expression of TLX1NB was up-regulated in colon cancer tissue. They confirmed that TLX1NB can promote the invasion, migration, and metastasis of colon cancer cells by promoting the phosphorylation of STAT5A and it also played an important role in regulating cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they concluded that TLX1NB may be an early biomarker for the recurrence of low-grade gliomas. Chen et al ( 46 ) found that the expression of TLX1NB was up-regulated in colon cancer tissue. They confirmed that TLX1NB can promote the invasion, migration, and metastasis of colon cancer cells by promoting the phosphorylation of STAT5A and it also played an important role in regulating cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There was an evident reduction in pulmonary metastatic nodules in experimental mice injected with TLX1NB-silenced-SW620 cells. Levels of p-STAT5A were found to be suppressed in the metastatic nodules from mice injected with TLX1NB-silenced-SW620 cells [ 64 ].…”
Section: Regulation Of Oncogenic Stat5 By Lncrnasmentioning
confidence: 99%